(untitled) (KULT_online, 2017)
Fotis Jannidis’, Hubertus Kohle’s, and Malte Rehbein’s current publication Digital Humanities. Eine Einführung (2017) delivers insight into the huge field of “Digital Humanities”. Clearly laid out, this introduction gathers the developments of the past 50 years in this interdisciplinary field of research. Due to the expertise of different professional representatives from the fields of literary studies, medieval studies, art history, historic-cultural information processing, library science, data studies, digital scholarly editing, and computer philology it provides valuable contributions for self-study.